2019
DOI: 10.21203/rs.2.15223/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Echocardiographic Assessment of Asymptomatic US Air Force Members with Early HIV Infection

Abstract: Objective People living with HIV (PLHIV) are at increased risk for cardiovascular disease (CVD) and development of subclinical echocardiographic abnormalities. In this study we describe the echocardiographic evaluations of asymptomatic US Air Force members who were diagnosed with HIV infection and evaluated at the San Antonio Military Medical Center between September 1, 2015 and September 30, 2016. Results Patients (n=50) were predominantly male (96%), mostly black (60%), with a mean age of 28 years. At HIV… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…[7,9,18,19] It has been reported in as low as 2% up to 85.7% of patients. [3,7,9,18–21] A recent systematic review reported pooled prevalence of 29.3%, a number similar to our study. [4] Similar to this study, increasing age has been shown to be an independent risk factor for DD in HIV patients [9] and is also a known risk factor in the general population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[7,9,18,19] It has been reported in as low as 2% up to 85.7% of patients. [3,7,9,18–21] A recent systematic review reported pooled prevalence of 29.3%, a number similar to our study. [4] Similar to this study, increasing age has been shown to be an independent risk factor for DD in HIV patients [9] and is also a known risk factor in the general population.…”
Section: Discussionsupporting
confidence: 90%
“…[4] There are some studies where ≤4% of the studied population had low ejection fraction. [2,3,20] The sensitivity of echocardiography for pulmonary hypertension is not satisfactory. Invasive tests may be required in patients with strong clinical suspicion as it is associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence ranging from 42.8% in India to as high as in 85.7% in Congo have been reported in the past (3,7,9,18,19). The lowest report of diastolic dysfunction was from a study on patients with early HIV infection of only 2% (20). Other studies report prevalence from 9.25% to 19.9% (2, 21) with a recent systematic review reporting pooled prevalence of 29.3%, a number similar to our study (4).…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review and meta-analysis published in 2018 showed the pooled prevalence of reduced ejection fraction below 50% was 12.3% which was more reduced in patients with AIDS showing the possible relation with immunode ciency and opportunistic infections and showed lower prevalence in patients on ART potentially explaining the preserved ejection fraction in our patients (4). There are some studies where four percent or less of the studied population had low ejection fraction (2,3,20).…”
Section: Discussionmentioning
confidence: 99%